EFEKTIVITAS PENGGUNAAN TEKNOLOGI VIRTUAL REALITY SEBAGAI MEDIA PROMOSI WISATA DI PULAU BAWEAN DENGAN METODE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Gayuh Afwa Maulana Alhasy; Mashuri, Chamdan; Setyo Permadi, Ginanjar; Muhammad Fatkhur Rizal (Inovate, 2024)
This study evaluates the effectiveness of Virtual Reality (VR) technology as a promotional medium fortourism in Bawean Island. The research aims to assess how VR can enhance tourist experiences andattract more visitors. The methodology employed is the Technology Acceptance Model (TAM). Theresults indicate that both TAM variables significantly contribute to user acceptance and satisfactionwith VR as a promotional tool. The findings suggest that integrating richer and more interactive VRcontent can enhance its effectiveness as a tourism promotion tool.Keyword: Virtual Reality, Technology Acceptance Model, tourism, Bawean Island, tourism promotion.